Study of the mechanism of high-efficient in-situ SO2 fixation during oxidative roasting of high‑sulfur iron ores and DFT calculation - Xiaojiao Chen; Yuming Ren; Wenjun Gao; Na Zhao (Fuel Processing Technology)
The development and utilization of high‑sulfur iron ore in China has provided abundant raw materials for the iron and steel industry, but it has also created severe environmental challenges, particularly in controlling sulfur dioxide emissions. Although the current sulfur-fixation technology has made some progress, it still has limitations such as low efficiency and less stability. This study will in-depth explore the mechanism of in-situ sulfur fixation with the aim of solving aforementioned issues and realizing the transition from terminal desulphurization to process control. Firstly, the effects of oxidation roasting temperature, oxygen concentration, gas flow rate and sulfur-fixation agent concentration on the sulfur-fixation efficiency were investigated to determine the regulation mechanism of sulfur fixation technology. Moreover, the sulfur-fixation activities of CaO and MgO were also compared in depth by Density Functional Theory (DFT) calculation in terms of surface adsorption energy, transition state and partitioned density of states (PDOS). Finally, the sulfur-fixation mechanism was analyzed in depth by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) tests in terms of phase composition, crystal structure and surface morphology. Therefore, the work will present basic theory and systematic guidance for in-site sulfur-fixation of high‑sulfur iron ore under oxidation roasting process.